Oral direct thrombin inhibitor as an alternative in the management of cerebral venous thrombosis: a series of 15 patients. Issue 7 (24th February 2015) - Mendonça, Marcelo D.; Barbosa, Raquel; Cruz‐e‐Silva, Vera; Calado, Sofia; Viana‐Baptista, Miguel
<x xml:space="preserve">Abstract</x> Background Cerebral vein thrombosis is a rare cause of stroke with significant risk of death and long‐term dependency. Anticoagulation has been associated with better long‐term prognosis, and vitamin K antagonists are usually prescribed in this setting. Aim The aim of this study was to present a series of 15 cerebral vein thrombosis patients treated with dabigatran. Methods Retrospective study of clinical, imaging, and follow‐up characterization of all patients admitted with cerebral vein thrombosis and treated with dabigatran in a tertiary neurology department between June 2011 and December 2013 was conducted. Complications and adverse effects were recorded. Modified Rankin Scale was used to assess clinical severity; excellent outcome was defined as modified Rankin Scale at six‐months of 0 to 1. Recanalization was assessed with an angiographic method (computer tomography, magnetic resonance imaging, or digital subtraction angiography). Results Eighteen patients were admitted for cerebral vein thrombosis. Dabigatran was started in 11 patients, and warfarin was started in 7. Four patients on warfarin were switched to dabigatran because of adverse effects at 0·5, 1, 3·5, and 4 months. A total of 15 patients were treated with dabigatran with median follow‐up time of 19 months. Excellent outcome was observed in 87% of patients and recanalization in 80%. Conclusions We report the largest series of cerebral vein thrombosis patients treated with dabigatran. Clinical outcome was excellent in most patients and not different from other studies. Dabigatran could possibly be considered an alternative to warfarin; nevertheless, further prospective assessment with randomized controlled studies is warranted.